If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m + -2 = 4 + m Reorder the terms: -2 + 5m = 4 + m Solving -2 + 5m = 4 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. -2 + 5m + -1m = 4 + m + -1m Combine like terms: 5m + -1m = 4m -2 + 4m = 4 + m + -1m Combine like terms: m + -1m = 0 -2 + 4m = 4 + 0 -2 + 4m = 4 Add '2' to each side of the equation. -2 + 2 + 4m = 4 + 2 Combine like terms: -2 + 2 = 0 0 + 4m = 4 + 2 4m = 4 + 2 Combine like terms: 4 + 2 = 6 4m = 6 Divide each side by '4'. m = 1.5 Simplifying m = 1.5
| -x-111+10x=33 | | -5x-6y-6x+7y= | | -5x-6y-6x+7= | | (7u^3-u^2-7)+(2u^3-4u^2)= | | 18x-8=-24 | | 0.80x=94 | | -3x^2+600x-3375=0 | | .50x+3+.80=1.80 | | 3b+1+b=2b+9 | | 3(y+2)=y+14 | | -9x-101-3x=79 | | 8x^2y+-5yx^2= | | 0.02x=5 | | x^2-200x+1125=0 | | (-a+5c)+(-7a+2c+3)= | | w+5.3=10.1 | | 25b+15= | | 7+(6x-5)4-30x= | | 9.2x-1.6x=28 | | -6+3x-22=23 | | 3(p+5)-8+11p= | | n-3n+8=5+n | | (2y^2+9y+4)+(-3y^2-3y-9)= | | x+4-7=24 | | xv-w=6 | | -3x+18=12 | | 7x+0.5y=-2 | | -8x-x=18 | | 2x-8=2+5x | | -124+3x+5x=84 | | 10+-13x+3x^2=0 | | (3a^2+2a+8)+(5a^2-a)= |